Minimization of cutting force, temperature and surface roughness through GRA, TOPSIS and Taguchi techniques in end milling of Mg hybrid MMC. (February 2018) - Gopal, P.M.; Soorya Prakash, K.
Graphical abstract: Highlights: End milling of hybrid magnesium MMC (Mg + E-Waste CRT + BN). Cutting forces, temperature and surface roughness were measured. Effect of reinforcement, tool and machining factors in milling is explained. Multi objective optimization through GRA and TOPSIS. Amount of reinforcement and its size have noteworthy effect in MMC machining. Abstract: Present study investigates the effect of material and machining parameters on cutting force, surface roughness and temperature in end milling of Magnesium (Mg) Metal Matrix Composite (MMC) using carbide tool. Mg hybrid composite was fabricated by reinforcing Cathode Ray Tube (CRT) panel glass, an intensifying E-waste and Boron Nitride (BN) particles through powder metallurgy method. The milling experiments were conducted based on L27 orthogonal array designed by considering CRT glass particle size and weight percentage, tool diameter, speed, feed and depth of cut as input process parameters. Multi objective optimization was done through Grey Relational Analysis (GRA) and Techniques for Order Preferences by Similarity to Ideal Solution (TOPSIS). Both of the techniques provided a similar optimum parameter condition i.e. 10 µm particle size, 5% reinforcement, 8 mm diameter tool, 710 rpm speed, 20 mm/min feed and 0.5 mm depth of cut that outcomes in 139.48 N in-feed force, 63.92 N cross-feed force, 42.6 N thrust force, 68.96 °C temperature and 0.198 µm surface roughness. ANOVA is performed to identify significance and also the effect of each process variables on response parameters. Though all the parameters were found to be significant, reinforcement weight% and particle size affects the response parameters as that of machining parameters whereas speed turned to be the least significant factor.